2022
DOI: 10.1093/rheumatology/keac089
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and cellular response to COVID-19 vaccination in patients with autoimmune inflammatory rheumatic diseases under real-life conditions

Abstract: Objectives Successful vaccination is key to overcoming the COVID-19 pandemic. Immunosuppressive medication is known to potentially compromise vaccination responses, and expansion of our knowledge on vaccination efficacy in patients with autoimmune inflammatory rheumatic diseases (AIIRD) is therefore of utmost importance. Methods We conducted a single-centre observational study and evaluated the efficacy of approved COVID-19 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 35 publications
(32 reference statements)
2
36
0
4
Order By: Relevance
“…Medications taken were not analysed. This may have influenced the underestimation of reported comorbidities with a significant impact on the response to vaccination [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Medications taken were not analysed. This may have influenced the underestimation of reported comorbidities with a significant impact on the response to vaccination [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rasselt et al showed that Rituximab administration was particularly frequently associated with a lack of seroconversion (90%), whereas Mycophenolate-mofetil (25%) had a lesser impact. However, additional negative effects of immunosuppressive co-medication should not be neglected [ 24 ]. B-cell repopulation and time between last Rituximab treatment prior to vaccination seems to be crucial as König et al and others demonstrated [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only 62% of patients with RMDs on treatment with MTX achieved adequate antibody production post immunization, whereas those on TNFi demonstrated an immune response similar to that of the healthy controls (>90%) [ 2 , 5 ]. In addition, it was found that not only humoral immunity, but cellular immunity is important for protection against COVID-19 [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, treatment with rituximab has been related to more severe disease and adverse outcome [ 1 ]. In addition, patients on rituximab failed to mount a sufficient immunogenic response to the two-dose immunization scheme with the mRNA vaccines, hence current guidelines suggest either postponing immunization or administering vaccines prior to initiation of treatment [ 2 ]. Adherence to personal protection measures and mass vaccination were shown to be the two most effective strategies for controlling the COVID-19 pandemic [ 3 ].…”
Section: Introductionmentioning
confidence: 99%